Genetic analysis of grain yield and related traits of extra-early orange maize inbred lines and their hybrids under drought and rain-fed conditions - Bonkoungou, Tégawendé Odette; Badu-Apraku, Baffour; Adetimirin, Victor Olawale; Nanema, Kiswendsida Romaric; Adejumobi, Idris Ishola (Frontiers in Plant Science, 2024)
Background: Orange maize genotypes are sources of provitamin A (PVA) carotenoids, which are precursors of vitamin A. PVA deficiency and drought constitute major challenges causing increasing food and nutritional insecurity in sub-Saharan Africa (SSA). Breeding of drought-tolerant provitamin A hybrid maize can mitigate these challenges. This study was undertaken to determine the combining ability of newly developed extra-early orange inbreds for grain yield and related traits under managed drought stress and rain-fed conditions, determine the mode of gene action conditioning the inheritance of the traits, and classify the inbreds into heterotic groups. Methodology: One hundred and ninety-six extra-early orange hybrids comprising 180 testcrosses, 10 single crosses, and 6 commercial checks were evaluated under managed drought and rain-fed conditions at Ikenne. In addition, 41 inbreds comprising 36 orange lines and 5 PVA testers involved in the hybrid development were assessed under drought and rain-fed conditions. Results: The means square for general combining ability (GCA) and specific combining ability (SCA) were significant for grain yield and most other traits under both growing conditions. The contributions of GCA to performance were larger than SCA in each growing condition. Broad-sense and narrow-sense heritability estimates for grain yield were 66 % and 37 % under managed drought and 88 % and 32 % under rain-fed conditions, respectively. Mid-parent heterosis and better-parent heterosis for grain yield were 338 % and 247 % under managed drought, while 173 % and 137 % under rain-fed conditions. Significant positive correlations existed among grain yield of hybrids, heterosis, and specific combining ability under managed drought. The 41 inbred lines were classified into three heterotic groups under both growing conditions. Sixteen testcross hybrids outyielded the best commercial check under managed drought. The testcross hybrids have great potential for commercialization to address the problem of drought and PVA deficiency in SSA. Inbred TZEEIOR 510 showed desirable GCA effects for grain yield and 04 other traits under drought.